2019
DOI: 10.3389/fimmu.2018.03050
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α Activation in Bone Marrow-Derived Dendritic Cells Modulates Innate Recognition of Melanoma Cells and Favors CD8+ T Cell Priming

Abstract: The IRE1α/XBP1s signaling pathway is an arm of the unfolded protein response (UPR) that safeguards the fidelity of the cellular proteome during endoplasmic reticulum (ER) stress, and that has also emerged as a key regulator of dendritic cell (DC) homeostasis. However, in the context of DC activation, the regulation of the IRE1α/XBP1s axis is not fully understood. In this work, we report that cell lysates generated from melanoma cell lines markedly induce XBP1s and certain members of the UPR such as the chapero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Bone marrow-derived DCs (BMDCs) show similar characteristics to moDCs, which differentiate from myeloid cells under the presence of granular colony-stimulating factor (GM-CSF). Both moDCs [57,58] and BMDCs [59,60] show efficient CP capacity to activate naïve CD8 + T cells, similar to cDC1s. Further, in mice, they efficiently activate naïve CD8 + T cells for pinocytosis [61], less efficiently for receptor-mediated endocytosis, and not at all for phagocytosis [38].…”
Section: Subsetsmentioning
confidence: 95%
“…Bone marrow-derived DCs (BMDCs) show similar characteristics to moDCs, which differentiate from myeloid cells under the presence of granular colony-stimulating factor (GM-CSF). Both moDCs [57,58] and BMDCs [59,60] show efficient CP capacity to activate naïve CD8 + T cells, similar to cDC1s. Further, in mice, they efficiently activate naïve CD8 + T cells for pinocytosis [61], less efficiently for receptor-mediated endocytosis, and not at all for phagocytosis [38].…”
Section: Subsetsmentioning
confidence: 95%
“…However, specific roles of UPR branches in brain residing DCs need to be further investigated (118). Pharmacological inhibition of IRE1α endonuclease function selectively blocks cross-presentation of tumor-associated antigen to major histocompatibility complex class I pathway without impairing presentation of tumor antigens to major histocompatibility complex class II, leading to inhibition of CD8 + T-cell priming (119). These contrasting observations draw attention to the potential pitfalls in connecting ER stress in DCs to diseases ( Table 1).…”
Section: Dendritic Cellmentioning
confidence: 99%
“…However, a different set of experiments demonstrated that recognition of melanoma cell lysates potently activated the IRE1/XBP1s axis in MoDCs, which increased the production of IL-6 and TNF and promoted cross-presentation of tumor-associated Ags in vitro [106]. Inhibition of IRE1 RNase activity, either through pharmacological blockade or by genetic deletion of the RNase domain, resulted in reduced cross-presentation of melanoma-associated Ags [106]. This evidence indicated that activation of IRE1 RNase in MoDCs contributed to effective CD8 + T cell activation.…”
Section: Monocyte-derived Dcs (Modcs)mentioning
confidence: 99%
“…cDCs can be partially recapitulated in in vitro cultures of bone marrow cells containing FMS-like tyrosine kinase 3 ligand FLT3L [121]. In these cultures, inhibition of IRE1 RNase resulted in reduced cross-presentation of tumor-associated Ags in vitro and decreased the production of proinflammatory cytokines in response to exposure to tumor cell lysates [106]. IRE1 RNase blockade in cDC1 equivalents from FLT3-L-containing cultures resulted in lower expressions of surface MHC Class I/ peptide complexes and reduced IL-12 production upon recognition of tumor cell lysates, which accompanied the reduced cross-presentation abilities [106].…”
Section: Cdcsmentioning
confidence: 99%
See 1 more Smart Citation